FROM DIGITALIZATION TO INTELLIGENCE: MAPPING AI FORECASTING READINESS OF MSMES IN GREATER JAKARTA - Hani Fitria Rahmani; Ratih Pratiwi; Eka Merdekawati; Aulia Hidayati; Mela Nurdialy (ZILLZELL MEDIA PRIMA, 2025)
Digital transformation presents both challenges and opportunities for Indonesian micro, small, and medium enterprises (MSMEs) in achieving sustainability performance. This study aims to examine the influence of digital readiness, technology adoption, and institutional support on MSMEs’ sustainability performance. A quantitative approach was employed by distributing questionnaires to MSME actors and analyzing the data using structural equation modeling based on partial least square (PLS-SEM). The results indicate that most independent variables have a positive and significant effect on sustainability performance, although certain variables show a negative relationship, which differs from some previous studies. This finding highlights that digital readiness and technology adoption do not always generate uniform effects but are strongly shaped by institutional contexts and internal conditions of MSMEs. Theoretically, this research contributes to the advancement of Institutional Theory and the Natural Resource-Based View (NRBV) by emphasizing digital capabilities as strategic resources for sustaining competitive advantage. Practically, the study suggests that policymakers and stakeholders should enhance digital literacy, infrastructure, and support programs for MSMEs to strengthen their ability to adapt to the digital era. The study concludes that synergy between internal MSME factors and external support is crucial for achieving sustainable business outcomes. Future research is recommended to include moderating variables such as strategic leadership or market orientation to provide deeper insights into the dynamics of MSME digital transformation.